Fish peduncle response during forward and backward propulsion. (10th February 2023) - Alam, Md. Mahbub
Fish is the master of fluid control, with high propulsive efficiency and great maneuverability. Carps are chosen for observations since they are the typical carangiform fish. We add some external stimuli on the fish and observe their responses. It is found that a fish attempts to escape backward or forward depending on the stimuli. The fish tries a greater number of its tail oscillations in a forward escape than in a backward escape. In the case of a forward escape, the retract stroke where the tail gets a concave shape (suitable for higher thrust generation) is faster than the forward stroke where the tail takes a convex shape (suitable for smaller drag), while vice versa in the case of a backward escape. Becoming concave or convex shapes of the tail and being faster or slower strokes all correspond to enhancing fluid momentum in the forward or backward directions where appropriate. The traveling wave of the body propagates backward and forward for the forward and backward escapes, respectively. The results provide a reference for bionic fish design and simulation.